2022
DOI: 10.3389/fpsyt.2021.787097
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine in Autism Spectrum Disorders—Focus on D2/D3 Partial Agonists and Their Possible Use in Treatment

Abstract: Autism spectrum disorders (ASD) are a group of disorders characterized by impairment in social communication and repetitive and stereotyped behaviors. ASD etiology is very complex, including the effect of both genetic and environmental factors. So far, no specific treatment for the core symptoms of ASD has been developed, although attempts have been made for the treatment of repetitive behavior. The pharmacological treatment is aimed at treating non-specific symptoms such as irritability and aggression. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 81 publications
0
33
1
Order By: Relevance
“…Brain regions that are sensitive to prenatal hypoxia include the cortex, basal ganglia (includes the nigrostriatal pathway), and white matter in children [78]. The nigrostriatal pathway is integral for many behaviors, such as motor function, cognition, social interactions, mood (anxiety/depression), reward, and attention [79][80][81]. Therefore, impairments of the nigrostriatal pathway can have long-term consequences, such as many neuropsychiatric disorders (e.g., Parkinson's disease [78,82], addiction [78], cognitive dysfunction [78], autism spectrum disorders [78,79], mood disorders [78,79,81], and attention deficit hyperactivity disorders [80]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain regions that are sensitive to prenatal hypoxia include the cortex, basal ganglia (includes the nigrostriatal pathway), and white matter in children [78]. The nigrostriatal pathway is integral for many behaviors, such as motor function, cognition, social interactions, mood (anxiety/depression), reward, and attention [79][80][81]. Therefore, impairments of the nigrostriatal pathway can have long-term consequences, such as many neuropsychiatric disorders (e.g., Parkinson's disease [78,82], addiction [78], cognitive dysfunction [78], autism spectrum disorders [78,79], mood disorders [78,79,81], and attention deficit hyperactivity disorders [80]).…”
Section: Discussionmentioning
confidence: 99%
“…The nigrostriatal pathway is integral for many behaviors, such as motor function, cognition, social interactions, mood (anxiety/depression), reward, and attention [79][80][81]. Therefore, impairments of the nigrostriatal pathway can have long-term consequences, such as many neuropsychiatric disorders (e.g., Parkinson's disease [78,82], addiction [78], cognitive dysfunction [78], autism spectrum disorders [78,79], mood disorders [78,79,81], and attention deficit hyperactivity disorders [80]). These relationships have also been observed in clinical studies examining children exposed to gestational hypoxia (pre-eclampsia, acute perinatal hypoxic injury, and gestational sleep apnea [1][2][3][4][5]).…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculated that these complementary clinical effects of a dopamine agonist and a dopamine antagonist might be related to similar actions on dopamine autoreceptors, regulating the dopaminergic hyperactivity that has been postulated in ASD ( Dollfus, 1992 ; Dollfus et al, 1993 ). Although dopaminergic dysfunction in ASD has been widely reported, especially in the midbrain dopaminergic system, the mechanisms are not fully understood ( Pavăl and Miclutia, 2021 ; Mandic-Maravic et al, 2022 ). Interestingly, both dopamine D2 receptor agonists (pramipexole, piribedil) and an antagonist (the antipsychotic drug fluspirilene) were among the drugs showing opposite gene expression perturbations in drug versus ASD at p < 0.1 and interacting with the dopamine D2 receptor gene.…”
Section: Discussionmentioning
confidence: 99%
“…There is also biological plausibility as both conditions may share similar pathophysiologic mechanisms. Both animal and human studies have demonstrated dopaminergic dysregulation in ASD, which is central to the pathogenesis of PD, [8][9][10] Moreover, these studies have identified dopamine receptors to be potential drug targets, though more research must be done to confirm this hypothesis. 8 Despite reports linking ASD with parkinsonian-like features, there has not been a systematic review of the clinical, genetic, and pathophysiologic data on the association between the two conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There is also biological plausibility as both conditions may share similar pathophysiologic mechanisms. Both animal and human studies have demonstrated dopaminergic dysregulation in ASD, which is central to the pathogenesis of PD, 8 , 9 , 10 Moreover, these studies have identified dopamine receptors to be potential drug targets, though more research must be done to confirm this hypothesis. 8 …”
Section: Introductionmentioning
confidence: 99%